2010
DOI: 10.1164/rccm.201001-0010oc
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Reduce Inflammation while Enhancing Bacterial Clearance and Improving Survival in Sepsis

Abstract: These data demonstrate that MSCs have beneficial effects on experimental sepsis, possibly by paracrine mechanisms, and suggest that immunomodulatory cell therapy may be an effective adjunctive treatment to reduce sepsis-related morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
582
4
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(626 citation statements)
references
References 45 publications
30
582
4
10
Order By: Relevance
“…MSCs also seem to attenuate end-organ infl ammatory damage. 40 Intravenous MSCs improve lung histology and decrease concentrations of proinfl ammatory cytokines in BAL fl uid after infection, 28,38 decrease concentrations of infl ammatory cytokines in cardiac tissue and improve cardiac function after intravenous LPS, 36 and also lower renal expression of proinfl ammatory cytokines and improve serological markers of kidney function after caecal ligation and puncture. 37 These eff ects occurred without substantial MSC localisation to the studied tissue, which suggests a paracrine mechanism.…”
Section: Injury Model Msc Source Msc Delivery Methods Major Fi Nding Ementioning
confidence: 99%
See 1 more Smart Citation
“…MSCs also seem to attenuate end-organ infl ammatory damage. 40 Intravenous MSCs improve lung histology and decrease concentrations of proinfl ammatory cytokines in BAL fl uid after infection, 28,38 decrease concentrations of infl ammatory cytokines in cardiac tissue and improve cardiac function after intravenous LPS, 36 and also lower renal expression of proinfl ammatory cytokines and improve serological markers of kidney function after caecal ligation and puncture. 37 These eff ects occurred without substantial MSC localisation to the studied tissue, which suggests a paracrine mechanism.…”
Section: Injury Model Msc Source Msc Delivery Methods Major Fi Nding Ementioning
confidence: 99%
“…37,38,[48][49][50][51] This antibacterial eff ect is partly mediated by improved phagocytic activity of host immune cells such as macrophages, 38,41 monocytes, 48 neutrophils, 49 and ITGAMpositive cells (monocytes, macrophages, and neutrophils). 38 Studies using ex-vivo human lungs have reported similar fi ndings. MSCs reduced alveolar bacterial counts and improved alveolar macrophage phagocytosis after direct bacterial injury.…”
Section: Antimicrobial Eff Ectsmentioning
confidence: 99%
“…Pathophysiologic mechanisms of ALI and ARDS include inflammation and increased endothelial and epithelial permeability to protein, resulting in extravascular accumulation of protein-rich edema fluid and alveolar epithelial injury (1). Several preclinical studies have demonstrated that bone marrow-derived mesenchymal stem (stromal) cells (MSCs) reduce the severity of ALI induced by endotoxin (2,3), live Escherichia coli bacteria (4,5), or following sepsis (6)(7)(8). Much of the therapeutic benefit of MSCs appears to derive from the release of paracrine soluble factors, which stabilize the injured alveolar epithelium and lung endothelium, reduce inflammation, increase the absorption of pulmonary edema fluid, and have antimicrobial activity (9).…”
mentioning
confidence: 99%
“…[31][32][33] This therapeutic effect may include transdifferentiation of MSCs into hepatocytelike cells, secretion of anti-inflammatory factors, and hepatocyte regeneration promotion at the site of injury. [34][35][36] Interestingly, Bruno's group confirmed that microvesicles derived from MSCs could protect against acute renal tubular injury via cell-tocell communication. 37,38 Exosomes/microvesicles contain mRNAs, microRNAs, and proteins, and our previous work indicated that hucMSCs and hucMSC-Ex can alleviate CCl 4 -inducued liver injury as that observed in hucMSCs, 10,39 suggesting that MSC-derived exosomes may be critical to reversing liver injury.…”
Section: Discussionmentioning
confidence: 99%